Cross-cultural perspective of FL teaching and learning in the Polish context - Sobkowiak, Paweł (Studies in Second Language Learning and Teaching, 2012)
This study examines whether learners’ capacity to use a foreign language (FL) successfully in the global world is developed in the FL classroom in Polish high schools. The article reports results of the quantitative research which aimed at assessing whether and to what extent homogeneous FL classes in Poland are conducive to developing learners’ intercultural (IC) sensitivity and competence. The results obtained from the two study samples, namely learners and teachers, are contradictory: In the students’ opinion, IC teaching/learning plays a marginal role, whereas the teacher respondents claim they practice IC teaching moderately. Thus, to be able to get a broader picture of IC teaching/learning in Poland the current research should be complemented by a separate qualitative study, that is, lesson observations and interviews with teachers and students. Only then could more valid conclusions be drawn.